Analysis of Eco-Enzyme Potential to Reduce BOD, COD, Oil and Grease Concentrations in Raw Water for Treated Water in Karawang: A Laboratory Experiment - Gina Lova Sari; Wilma Nurrul Adzillah; Kania Ratnawati; Devita Fitria Alam Sari; Saidah Saidah (Gema Lingkungan Kesehatan, 2025)
Organic pollutants are produced by domestic household waste, so eco-enzymes are potentially used as bioremediation agents for community-based water quality and pollution control, as has been conducted in the Citarum Harum Program. However, scientific information regarding eco-enzymes characteristics and their ability to degrade BOD, COD, and oil and grease is limited, especially in surface water used for raw water for treated water. This research examines eco-enzymes potential as biocatalysts to reduce BOD, COD, and oil and grease in raw water for treated water in Karawang primary irrigation canals. Water samples were collected from Karawang primary irrigation canals according to the Indonesian National Standard No. 8995:2021. Meanwhile, the eco-enzyme is made from fruit peel and molasses for 624 days. The experiments were carried out with five variations of raw water and eco-enzymes mixtures (v/v) of 3,000.00:0.00 mL; 2,900.00:100.00 mL; 2,850.00:150.00 mL; 2,800.00:200.00 mL; and 2,750.00:250.00 mL with a batch flow system for ten days. The results showed that eco-enzymes contained protease, amylase, and lipase as much as 1,231.00 U/mL; 4.00 U/mL; and 9.69 U/mL, respectively, with a pH of 3.80. The concentrations of BOD, COD, and oil and grease in the current study tended to increase from 222.00 mg/L; 1,047.00 mg/L, and 2.20 mg/L to 505.00-593.00 mg/L; 1245.50-1941.50 mg/L; and 6.60-9.00 mg/L, respectively, which might be due to the addition of organic compounds through mixing eco-enzymes that makes the biodegradation process takes longer. These results indicate that eco-enzymes are less appropriate for surface water treatment with continuous flow systems and more suitable for biological treatment of communal wastewater in batch flow systems.